2020
DOI: 10.1093/pm/pnaa018
|View full text |Cite
|
Sign up to set email alerts
|

Risk of New Fractures in Vertebroplasty for Multiple Myeloma. A Retrospective Study

Abstract: Objective Vertebroplasty is a percutaneous minimally invasive procedure indicated for vertebral collapse pain treatment. Among the known complications of the procedure is the augmented risk of new vertebral fractures. There are no specific studies in this patient population describing the risk of new vertebral fractures after vertebroplasty. This study analyzed risk factors associated with new vertebral fractures after vertebroplasty in patients with multiple myeloma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, polymethylmethacrylate (PMMA) bone cement lacked osseointegration ability, which could easily lead to loosening and displacement, causing postoperative adjacent vertebra fractures and recompression fractures, thereby requiring further surgical intervention [7][8][9]. A retrospective study found that the incidence of cement displacement was about 18.20%, and the time of post-operative cement displacement ranged from 1.8 to 38.2 months [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, polymethylmethacrylate (PMMA) bone cement lacked osseointegration ability, which could easily lead to loosening and displacement, causing postoperative adjacent vertebra fractures and recompression fractures, thereby requiring further surgical intervention [7][8][9]. A retrospective study found that the incidence of cement displacement was about 18.20%, and the time of post-operative cement displacement ranged from 1.8 to 38.2 months [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, PMMA bone cement lacks osseointegration ability and has a higher elastic modulus, which could easily lead to loosening and displacement of bone cement, cause postoperative adjacent vertebra fractures and re-compression fractures, thereby requiring further surgical intervention [ 7 , 8 ]. The incidence of new fractures has been reported to be 5.0–22.0% and 17.2–52.0% in 1 and 4 years postoperatively, respectively [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%